Characterisation of Glucose-Dependent Insulinotropic Polypeptide Receptor Antagonists in Rodent Pancreatic Beta Cells and Mice. (September 2019) - Perry, RA; Craig, SL; Ng, MT; Gault, VA; Flatt, PR; Irwin, N
Hypersecretion and alterations in the biological activity of the incretin hormone, glucose-dependent insulinotropic polypeptide (GIP), have been postulated as contributing factors in the development of obesity-related diabetes. However, recent studies also point to weight-reducing effects of GIP receptor activation. Therefore, generating precise experimental tools, such as specific and effective GIP receptor (GIPR) antagonists, is of key significance to better understand GIP physiology. Thus, the primary aim of the current study was to uncover improved GIPR antagonists for use in rodent studies, using human and mouse GIP sequences with N- and C-terminal deletions. Initial in vitro studies revealed that the GIPR agonists, human (h) GIP(1-42), hGIP(1-30) and mouse (m) GIP(1-30), stimulated ( P < 0.01 to P < 0.001) insulin secretion from rat BRIN-BD11 cells. Analysis of insulin secretory effects of the N- and C-terminally cleaved GIP peptides, including hGIP(3-30), mGIP(3-30), h(Pro 3 )GIP(3-30), hGIP(5-30), hGIP(3-42) and hGIP(5-42), revealed that these peptides did not modulate insulin secretion. More pertinently, only hGIP(3-30), mGIP(3-30) and h(Pro 3 )GIP(3-30) were able to significantly ( P < 0.01 to P < 0.001) inhibit hGIP(1-42)-stimulated insulin secretion. The human-derived GIPR agonist sequences, hGIP(1-42) and hGIP(1-30), reduced ( P < 0.05) glucose levels in mice following conjoint injection with glucose, but mGIP(1-30) was ineffective. None of the N- and C-terminally cleaved GIP peptides affected glucose homeostasis when injected alone with glucose. However, hGIP(5-30) and mGIP(3-30) significantly ( P < 0.05 to P < 0.01) impaired the glucose-lowering action of hGIP(1-42). Further evaluation of these most effective sequences demonstrated that mGIP(3-30), but not hGIP(5-30), effectively prevented GIP-induced elevations of plasma insulin concentrations. These data highlight, for the first time, that mGIP(3-30) represents an effective molecule to inhibit GIPR activity in mice.